2008
DOI: 10.1159/000113710
|View full text |Cite
|
Sign up to set email alerts
|

Galanin Hyperinnervation Upregulates Choline Acetyltransferase Expression in Cholinergic Basal Forebrain Neurons in Alzheimer’s Disease

Abstract: Background: Fibers containing galanin (GAL) enlarge and hyperinnervate cholinergic basal forebrain (CBF) nucleus basalis (NB) neurons in late-stage Alzheimer’s disease (AD), yet the physiological consequences of this phenomenon are unclear. Objective: To determine whether GAL hyperinnervation of cholinergic NB neurons modulates the expression of genes critical to cholinergic transmission [e.g. acetylcholine (ACh) metabolism and ACh receptors] in AD. Methods: Single-cell gene expression profiling was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
5
37
0
Order By: Relevance
“…By contrast, there is no evidence for GAL fiber [22,23] or GALR [26,27] overexpression within the posterior NB subfields where cholinergic neuron degeneration is greatest [93,94]. In addition to the custom cDNA array data presented above showing reduced expression of PP subunits in single cholinergic NB neurons hyperinnervated by GAL, which potentially slows NFT formation, we have also used this technique to show that ChAT mRNA levels are selectively increased in GAL-hyperinnervated NB neurons in AD compared to non-innervated NB neurons in control or AD brains [34] (Fig. 3).…”
Section: Galanin Plasticity As a Neuroprotective Factor In Admentioning
confidence: 95%
See 1 more Smart Citation
“…By contrast, there is no evidence for GAL fiber [22,23] or GALR [26,27] overexpression within the posterior NB subfields where cholinergic neuron degeneration is greatest [93,94]. In addition to the custom cDNA array data presented above showing reduced expression of PP subunits in single cholinergic NB neurons hyperinnervated by GAL, which potentially slows NFT formation, we have also used this technique to show that ChAT mRNA levels are selectively increased in GAL-hyperinnervated NB neurons in AD compared to non-innervated NB neurons in control or AD brains [34] (Fig. 3).…”
Section: Galanin Plasticity As a Neuroprotective Factor In Admentioning
confidence: 95%
“…These observations raise the possibility that GAL upregulation promotes cholinergic neuronal survival during the late stage of AD. In this regard, gene expression profiling of individual CBF neurons in AD tissue suggests that GAL hyperinnervation positively regulates mRNAs that promote cholinergic neuron function and survival [34,35]. This article reviews evidence supporting the concept that GAL overexpression plays a role in the survival of select neuronal populations associated with cognitive decline in AD.…”
Section: Introductionmentioning
confidence: 95%
“…8) This implies that the increase of the ChAT level in cholinergic neurons plays a critical role in cognition enhancement and thus the cholinergic gene locus "VAChT/ChAT" can be a putative target for therapeutic approaches on AD. [9][10][11] Several studies reported that ginsenosides (i.e., Rg1 and Rb1) isolated from ginseng are responsible for ginseng's effects on the central nervous system (CNS) and the peripheral nervous system. 12,13) The objective of this study is to investigate whether five representative ginsenosides (Rb1, Re, Rd, Rg1, and Rg3) have beneficial effects on the cholinergic system and also to examine the possible mechanisms of the most active ginsenosides.…”
mentioning
confidence: 99%
“…GAL inhibits cholinergic neurotransmission and GAL overexpression enhances AD progression (122). Overexpression of GAL in transgenic mice was associated with cognitive deficit, suggesting that increased expression levels of GAL may lead to neurochemical and cognitive impairments similar to those in AD (123).…”
Section: Galanin (Gal)mentioning
confidence: 99%